LASER CUTTING PROCESS OPTIMISATION IN FUNCTION OF THE SPEED AND POWER - Duncāns, Sandris; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
This article describes an experiment, which is basically the aim fix is possible with diode laser blue tone spectrum with his length and 5, 5W power 450nm, used for cutting plywood to 3, 48 mm in thickness. Before the experiment explored and found every possible literature (scientific articles, publications, producers of the discovery that scientists do not count as scientific articles and several books).Experiment created experimental stands on the existing compact home craftsmen to 600/2 Stepcraft CNC equipment with China produced in the diodes lasers with the power of 450nm 5, 5W module, measured outgoing power, doing experiment with cutting plywood, laser diodes program "optimum parameters and the method developed by diodes laser optimum for the location parameter.